A prospective observational study of the effects of sugammadex on peri‐operative oestrogen and progesterone levels in women who take hormonal contraception. (6th November 2022) - Devoy, T.; Hunter, M.; Smith, N. A.
Summary: Pharmacokinetic modelling suggests that sugammadex may interact with endogenous progesterone and reduce levels by 34% in patients taking hormonal contraception. Due to this potential interaction that may be equivalent to missing one dose of an oral contraceptive pill, both the manufacturer and professional anaesthesia organisations recommend counselling patients to use additional non‐hormonal contraception after administration of sugammadex. We performed a prospective observational study examining the changes in serum oestrogen and progesterone concentrations in premenopausal adult women undergoing an operative procedure. Sixty participants who were on hormonal contraception received sugammadex. Two additional control groups were recruited, consisting of 30 participants who were not on hormonal contraception and did not receive sugammadex, and 32 who were not on hormonal contraception and did receive sugammadex. Three blood samples were taken: before sugammadex; 15 min post‐sugammadex; and 240 min post‐sugammadex or end of operating theatre time. Median oestrogen levels decreased from baseline by around 40% at 240 min in all three groups (p ≤ 0.001). Progesterone levels rose significantly at 15 min (p = 0.002) in patients on contraception then decreased non‐significantly to 20% below baseline at 240 min. The decrease in oestrogen and the rise in progesterone could both act to minimise the risk of ovulation and thus protect contraception in this population. We found no evidence of a change in hormone levels that might threaten contraceptive efficacy in women on hormonal contraception receiving sugammadex.